Looking inside the black box: results of a theory-based process evaluation exploring the results of a randomized controlled trial of printed educational messages to increase primary care physicians’ diabetic retinopathy referrals [Trial registration number ISRCTN72772651] - Grimshaw, Jeremy M; Presseau, Justin; Tetroe, Jacqueline; Eccles, Martin P; Francis, Jill J; Godin, Gaston; Graham, Ian D; Hux, Janet E; Johnston, Marie; Légaré, France; Lemyre, Louise; Robinson, Nicole; et al. (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Theory-based process evaluations conducted alongside randomized controlled trials provide the opportunity to investigate hypothesized mechanisms of action of interventions, helping to build a cumulative knowledge base and to inform the interpretation of individual trial outcomes. Our objective was to identify the underlying causal mechanisms in a cluster randomized trial of the effectiveness of printed educational materials (PEMs) to increase referral for diabetic retinopathy screening. We hypothesized that the PEMs would increase physicians’ intention to refer patients for retinal screening by strengthening their attitude and subjective norm, but not their perceived behavioral control. Methods Design: A theory based process evaluation alongside the Ontario Printed Educational Material (OPEM) cluster randomized trial. Postal surveys based on the Theory of Planned Behavior were sent to a random sample of trial participants two months before and six months after they received the intervention. Setting: Family physicians in Ontario, Canada. Participants: 1,512 family physicians (252 per intervention group) from the OPEM trial were invited to participate, and 31.3% (473/1512) responded at time one and time two. The final sample comprised 437 family physicians fully completing questionnaires at both time points. Main outcome measures: Primary: behavioral intention related to referring patient for retinopathy screening; secondary: attitude, subjective norm, perceived behavioral control. Results At baseline, family physicians reported positive intention, attitude, subjective norm, and perceived behavioral control to advise patients about retinopathy screening suggesting limited opportunities for improvement in these constructs. There were no significant differences on intention, attitude, subjective norm, and perceived behavioral control following the intervention. Respondents also reported additional physician- and patient-related factors perceived to influence whether patients received retinopathy screening. Conclusions Lack of change in the primary and secondary theory-based outcomes provides an explanation for the lack of observed effect of the main OPEM trial. High baseline levels of intention to advise patients to attend retinopathy screening suggest that post-intentional and other factors may explain gaps in care. Process evaluations based on behavioral theory can provide replicable and generalizable insights to aid interpretation of randomized controlled trials of complex interventions to change health professional behavior. Trial registration ISRCTN72772651 .